Intramolecular N–Me and N–H aminoetherification for the synthesis of N-unprotected 3-amino-O-heterocycles. Issue 3 (5th January 2021) - Paudyal, Mahesh P.; Wang, Mingliang; Siitonen, Juha H.; Hu, Yimin; Yousufuddin, Muhammed; Shen, Hong C.; Falck, John R.; Kürti, László
Abstract : A mild Rh-catalyzed method for synthesis of cyclic unprotected N–Me and N–H 2, 3-aminoethers using an olefin aziridination–aziridine ring-opening domino reaction has been developed. Abstract : A mild Rh-catalyzed method for synthesis of cyclic unprotected N–Me and N–H 2, 3-aminoethers using an olefin aziridination–aziridine ring-opening domino reaction has been developed. The method is readily applicable to the stereocontrolled synthesis of a variety of 2, 3-disubstituted aminoether O-heterocyclic scaffolds, including tetrahydrofurans, tetrahydropyrans and chromanes.